FENOMENA PENITIPAN ORANG TUA LANSIA DI PANTI SOSIAL TRESNA WERDHA GAU MABAJI, KABUPATEN GOWA - Andi Kumalasari; Andi Agustang; Muhammad Syukur (Universitas Negeri Makassar, 2023)
Tresna Werdha Gau Mabaji Home is a safe place for the elderly because of their helplessness. One of them is the Tresna Werdha Gau Mabaji Nursing Home, Gowa Regency. When elderly parents are already in a nursing home, of course the functions performed by the family, such as protecting, caring for and providing affection, experience changes, because in a nursing home it is no longer the family that cares for the elderly but the orphanage staff. In this study, the focus was on children and parents who came from the city of Makassar, which was dominated by various ethnic groups. This study aims to determine the phenomenon of elderly parents' care in nursing homes and to analyze the background of a child's decision to leave their parents in a nursing home. This research includes a qualitative research approach and descriptive data types, using interview guidelines and documentation. Based on the results of observations and interviews at the Tresna Werdha Gau Mabaji Nursing Home, it shows that the phenomenon of caring for the elderly in nursing homes is no longer common due to the increasing number of elderly cared for each year. The reasons for children leaving their parents in nursing homes are dominated by economic factors and busyness so they cannot take care of their parents at home.Panti Sosial Tresna Werdha Gau Mabaji merupakan tempat yang aman bagi lansia karena ketidakberdayaan mereka. Salah satunya Panti Jompo Tresna Werdha Gau Mabaji Kabupaten Gowa. Ketika orang tua lansia sudah berada di panti jompo tentunya fungsi yang dilakukan oleh keluarga seperti, melindungi, merawat dan memberikan kasih saying mengalami perubahan, karena di panti jompo bukan lagi keluarga yang merawat lansia melainkan petugas panti. Dalam penelitian ini difokuskan kepada anak dan orang tua yang berasal dari Kota Makassar yang didominasi oleh berbagai jenis suku. Penelitian ini bertujuan untuk mengetahui fenomena penitipan orang tua lansia di panti jompo dan menganalisis latar belakang keputusan seorang anak menitipkan orang tuanya di panti jompo. Penelitian ini termasuk penelitian pendekatan kualitatif dan jenis data deskriptif, dengan menggunakan pedoman wawancara dan dokumentasi. Berdasarkan hasil observasi dan wawancara di Panti Jompo Tresna Werdha Gau Mabaji menunjukkan bahwa fenomena penitipan lansia di panti jompo sudah tak lazim lagi dikarenakan meningkatnya jumlah lansia yang dititip tiap tahunnya. Adapun alasan anak menitipkan orang tua mereka ke panti jompo di dominasi faktor ekonomi dan kesibukan sehingga mereka tidak dapat mengurus orang tua mereka dirumah.